Direct effects of ocean alkalinity enhancement in the Baltic Sea–results from in-silico experiments - Anschütz, Anna-Adriana; Lencina-Avila, Jannine M.; Rehder, Gregor; Cahill, Bronwyn; Neumann, Thomas; Radtke, Hagen (Frontiers in Climate, 2025)
To achieve carbon neutrality, ocean alkalinity enhancement (OAE) is currently being researched as a marine option for carbon dioxide removal (CDR). The approach of releasing calcite near the sediments and using the effect of enhanced mineral solubility in the pore water for more efficient dissolution may be promising in the Baltic Sea. The Baltic Sea is considered a potential application site for this method, as, in contrast to other seas, it is partly undersaturated in calcite even at shallow depths. However, the possible implications of this method, specifically if applied in coastal settings, are still poorly understood. Therefore, using a coupled hydrodynamic and biogeochemical ocean model of the Baltic Sea, we simulated the release of calcite near the sediment as a possible strategy for OAE. Simulations were run with and without enhanced solubility in the pore water for two release locations, one in shallow coastal water and one in a deep basin. While enhanced solubility by oxic mineralisation did not make a difference for the deep basin, it substantially changed the achievable calcite dissolution rates at the coastal site and therefore the potential CO2 removal. Here, our simulations provide a lower and an upper limit of the effectiveness of calcite dissolution. The release locations differed considerably in magnitude and timescales of CO2 uptake. As the saturation level of calcite appears to be the main limiting factor of the method, the CO2 removal potential of a release location cannot be upscaled infinitely by adding more calcite. Our results demonstrate a potential for OAE using calcite in the Baltic Sea. We used the model results on average and maximum changes in alkalinity and pH to reflect on potential environmental impacts based on a review of the existing literature. However, safe and responsible deployment of this CDR method in the Baltic Sea requires further research on localized dissolution rates, the alkalinity budget of the Baltic Sea and the environmental implications of OAE using calcite.